Unveiling the immunological landscape: comprehensive characterization of neoantigen-reactive immune cells in neoantigen cancer vaccines - Liu, Weijiang; Su, Hong; Guo, Peng; Hong, Liping; Hao, Xishan; Li, Xiaoling (Frontiers in Immunology, 2025)
Neoantigen-based cancer vaccine therapy represents a promising precision oncology strategy that targets unique tumor-specific mutations to elicit a robust immune response. This therapeutic approach is designed to harness the host’s immune response against tumor-specific neoantigens to eliminate cancer cells. The efficacy of neoantigen vaccines dependents on the coordinated action of diverse immune cells, including T lymphocytes, dendritic cells, B lymphocytes, natural killer cells, and macrophages. Each cell type plays a distinct and crucial role in recognizing, targeting, and destroying malignant cells. Understanding the mechanisms governing both individual and collective immune cell dynamics is crucial for therapeutic success. This comprehensive review systematically explores the mechanisms of neoantigen-specific immune cells, their dynamic interactions, and clinical application progress, aiming to unveil their potential value and future development in cancer treatment.